2011 IEEE International Symposium on Hardware-Oriented Security and Trust 2011
DOI: 10.1109/hst.2011.5955012
|View full text |Cite
|
Sign up to set email alerts
|

On improving reliability of delay based Physically Unclonable Functions under temperature variations

Abstract: Physically Unclonable Functions (PUFs) are a special class of circuits used for challenge-response authentication. The challenge-response pair for PUFs should be mathematically unpredictable, but must be reliable and remain unvarying. The reliability of PUFs implemented in CMOS circuits is frequently compromised by environmental conditions such as voltage and temperature. In this paper, we propose two methods for improving the reliability of delay based PUFs, by reducing temperature sensitivity. The first meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Results also showed that only SVC-OPC could generate longer keys that pass the NIST tests. While reliability was lower than P-OPC, it is better than the conventional approach (21% improvement) and could still be improved with variation-resistant circuit designs [11], [12].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Results also showed that only SVC-OPC could generate longer keys that pass the NIST tests. While reliability was lower than P-OPC, it is better than the conventional approach (21% improvement) and could still be improved with variation-resistant circuit designs [11], [12].…”
Section: Discussionmentioning
confidence: 86%
“…Some authors have also investigated better circuit designs and supply voltage biasing [9], [10] that enhance the random variations within the architecture for better PUF uniqueness and/or reliability. Circuit resistance to environmental variation has also been studied [10]- [12]. More recently, some groups have begun investigating ways to counteract systematic variations within the fabricated PUFs by adding compensation hardware to the PUF [13], [14].…”
Section: Introductionmentioning
confidence: 98%
“…Around 100,000 challenge-response pairs were generated under different operating conditions (0 − 75 • C and ±10%V dd ) for determining ΔT min distribution. There exist several circuit-and system-level techniques to improve the reliability of PUF circuits [19], [20]. Some of the common methods include error-correction codes, feedback based control (supply voltage, body-biasing etc.…”
Section: A Reliability Monitorsmentioning
confidence: 99%
“…Therefore, these experimental results demonstrate a good overall reproducibility of CF-ROPUF sample frequencies under varying temperatures and supply voltages. The reliability of our configurable PUF with different types of silicon PUFs that are suitable for FPGA [16], [55], [56] are compared in Table 4. Our CF-ROPUF shows a slightly better average reliability as compared to the other designs.…”
Section: ) Puf Reproducibilitymentioning
confidence: 99%